ANALISIS PENENTUAN SKALA PRIORITAS PEMELIHARAAN DAN PENINGKATAN RUAS JALAN KOTA DENGAN METODE AHP BERDASARKAN PENGADUAN PADA APLIKASI PRO DENPASAR - Adhiswari Wedagama, Dewa Ayu Trisna; Suthanaya, Putu Alit; Ariawan, I Made Agus (JURNAL SPEKTRAN; Vol 9 No 2 (2021)DO - 10.24843/SPEKTRAN.2021.v09.i02.p09, 2021)
Projects carried out by PT. Tunas Jaya Sanur during 2017 is quite diverse, so there is often a variety of potentials related to work safety and has an impact on the surrounding environment. Therefore, PT. Tunas Jaya Sanur implements the Safety, Occupational and Environmental Health Management System. In addition, the director of the company PT. Tunas Jaya also measures the achievement of Management of Occupational Health, Safety and Environment (SMK3L) by using a Key Performance Indicator (KPI). The purpose of this study is to find out work safety and environmental problems (K3L) and to determine the level of success that has been obtained by PT. Tunas Jaya Sanur during 2017 in terms of occupational and environmental safety risks (K3L) based on the main performance indicators (KPI) set by the company. Data collection was conducted using a questionnaire involving 88 respondents who were directly involved in the PT. Tunas Jaya Sanur during 2017. The method of analysis in this study is a quantitative analysis method carried out based on Australian / New Zealand (AS / NZS) standards 4360: 2004, then to measure KPI (Key Performance Indicators) on procedures for calculating KPIs main). The results of the analysis of risks issued by PT. Tunas Jaya is a medium risk (medium risk) of 30 risks, a large risk (high risk) of 14 risk-related risks (very high risk) are 2 risks. The level of success in controlling and controlling that has been done by PT. Tunas Jaya Sanur during 2017 showed that the work safety and environmental management (K3L) of PT. Tunas Jaya Sanur Bali in 2017 is classified as "Very Healthy", with the AA category with a performance score of 94.58%.